2007
DOI: 10.1038/nnano.2007.106
|View full text |Cite
|
Sign up to set email alerts
|

Real-time single-molecule imaging of oxidation catalysis at a liquid–solid interface

Abstract: Many chemical reactions are catalysed by metal complexes, and insight into their mechanisms is essential for the design of future catalysts. A variety of conventional spectroscopic techniques are available for the study of reaction mechanisms at the ensemble level, and, only recently, fluorescence microscopy techniques have been applied to monitor single chemical reactions carried out on crystal faces and by enzymes. With scanning tunnelling microscopy (STM) it has become possible to obtain, during chemical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
191
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(200 citation statements)
references
References 18 publications
7
191
0
2
Order By: Relevance
“…Such a distribution points at a correlated process, and might be explained by a similar preferential pair-wise generation of state Mn1-C (illustrated in Fig. 1) as was previously observed for the reaction of oxygen with another type of Mn porphyrins adsorbed on a Au(111) surface 18 . At higher surface coverages of Mn1-C of 10-16%, this correlation appears not so pronounced when compared to the corresponding simulation (Fig.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…Such a distribution points at a correlated process, and might be explained by a similar preferential pair-wise generation of state Mn1-C (illustrated in Fig. 1) as was previously observed for the reaction of oxygen with another type of Mn porphyrins adsorbed on a Au(111) surface 18 . At higher surface coverages of Mn1-C of 10-16%, this correlation appears not so pronounced when compared to the corresponding simulation (Fig.…”
supporting
confidence: 75%
“…The majority of these studies use ensemble techniques in solution, such as electrochemistry and absorption, electron paramagnetic resonance and nuclear magnetic resonance spectroscopy. The scanning tunneling microscope (STM) has proven to be a promising tool to study reactions at the molecular level [8][9][10][11][12] , and initial experiments have been reported in which the reactive properties of metal porphyrins were studied on a surface at the single molecule level by STM in ultrahigh vacuum (UHV) [13][14][15][16][17] and under ambient conditions 18,19 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that the latter phenomenon is likely always playing a role in the final mechanism. Recently, Elemans et al have demonstrated that in the presence of oxygen Mn-porphyrins physisorbed on Au (111) have different catalytic properties than their counterparts in solution, 3 thus giving the first indication that the physicochemical properties of functional porphyrins are modified upon physisorption. Moreover, since the n-dodecyl tails of the Zn-TDPs are solvated by n-tetradecane, coordination of the zinc core might be disfavored in solution.…”
Section: Scanning Tunneling Microscopy (Stm) All Experimentsmentioning
confidence: 99%